2006
DOI: 10.1213/01.ane.0000199399.04496.6d
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Test Temperature and Storage Temperature on Platelet Aggregation: A Whole Blood In Vitro Study

Abstract: We systematically evaluated the effects of test temperature and storage temperature on platelet aggregation using flow cytometry and impedance aggregometry. Aliquots of citrated whole blood from 27 healthy adult male volunteers were stored at 37 degrees C and 22 degrees C. Aliquots were subjected to impedance aggregometry in response to collagen, adenosine diphosphate, ristocetin, and arachidonic acid performed at 22 degrees C, 34 degrees C, 37 degrees C, and 40 degrees C. The expression of activated fibrinoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 22 publications
3
42
0
2
Order By: Relevance
“…Although the time span between withdrawal and analysis is of less importance, the measurement of labile blood components such as platelets should be performed within a reasonable time frame [18]. Storage temperature needs to be standardized because it modifies platelet reactivity [19]. Testing the aggregation response to all routine platelet agonists may be indicated in this setting in order to assess defects involving various intracellular pathways of platelet activation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the time span between withdrawal and analysis is of less importance, the measurement of labile blood components such as platelets should be performed within a reasonable time frame [18]. Storage temperature needs to be standardized because it modifies platelet reactivity [19]. Testing the aggregation response to all routine platelet agonists may be indicated in this setting in order to assess defects involving various intracellular pathways of platelet activation.…”
Section: Discussionmentioning
confidence: 99%
“…15 To date, MEA has proven sensitive for platelet inhibition induced by aspirin and clopidogrel, as well as for the effects of cardiopulmonary bypass (CPB) and of hypothermia on platelet aggregation. 14,[16][17][18] MEA usefulness in identifying groups of patients at a high risk of transfusion of platelet concentrates (PC) has not been investigated so far. Therefore, we performed a pilot study evaluating the predictive value of perioperative MEA measurements for PC transfusion in cardiac surgery.…”
mentioning
confidence: 99%
“…It has been suggested that platelets are also inhibited by hypothermia, and there are some studies supporting this notion (Michelson et al, 1994(Michelson et al, , 1999Frelinger et al, 2003). However, there are more recent reports suggesting increased platelet reactivity during mild hypothermia (Zhang et al, 2004;Lindenblatt et al, 2005;Scharbert et al, 2006;Xavier et al, 2007). We examined platelet activity at 33°C and 37°C and found unchanged or slightly increased platelet activity for most agonists (Hogberg et al, 2009).…”
Section: Coagulation and Platelet Functionmentioning
confidence: 81%